Evaluating Student Satisfaction and Preferences in Higher Education Online Learning: A Post-Pandemic Exploration - Tanguihan, Lucille (Journal of Interdisciplinary Perspectives, 2024)
This study, grounded in transformational learning theories, investigated the satisfaction levels of higher education students with online learning during the COVID-19 pandemic. The study found that students expressed a neutral sentiment towards the online learning environment, with key aspects valued by students, including instructor support, guidance, and personalization. However, students reported the lowest satisfaction with the knowledge and skills acquired, indicating a need to align teaching methods with desired learning outcomes. Facility performance also received a neutral mean satisfaction score. Students appreciated webinars, seminars, and extracurricular activities, recognizing their importance in enriching online education. However, they wanted more than school-provided facilities, suggesting physical resources and service improvements. Regarding future learning modes, students preferred blended classrooms, face-to-face instruction, and specific online teaching platforms over exclusive online classes, emphasizing the need for diversified learning approaches and effective digital tools. A notable finding was the positive correlation between students' willingness to recommend online learning in the future and their overall satisfaction, underscoring the importance of instructor engagement, diverse learning modalities, and aligning teaching methods with desired learning outcomes to meet the evolving needs of students in a post-pandemic educational landscape. These findings have significant implications for the future of higher education, particularly in the design of online learning platforms and the role of educators in enhancing the student experience.